ULTRASONOGRAPHY AS SCREENING TOOL FOR BREAST CANCER IN YOUNG WOMEN UNDER 40 YEARS OLD - Alfarossi, Osy Lu'lu; Kusumawardani, Fernanda; Putri, Vika Annisa (Essential: Essence of Scientific Medical Journal, 2021)
Introduction: Breast cancer’s incidence in Indonesia is 42.1/100.000 women. And incidence for women under 40 years old is 13%. It’s not very common for young women to do breast cancer screening unless they have higher risk and come to physician with symptoms or breast lump. Screening recommended for young women is magnetic resonance imaging (MRI). But MRI screening is more expensive thus USG screening also used as screening alternative for breast cancer in young women. Discussion: Breast cancer in young women is not common but more aggressive, have poor prognosis, also have a higher risk of recurrency and mortality. Screening is needed to decrease mortality rate and the gold standard for breast cancer screening is mammography. But the breast density in young women is higher and it is difficult to detect with mammography so USG or MRI is used instead. Some guidelines recommend using USG with comparable sensitivity and specificity as mammography. Conclusion: USG is a potential and effective tool for breast cancer screening in young women.